Payr’s disease: a rare cause of abdominal pain syndrome in children - Cherkavskyi, Ievhen; Sliusar, Nataliia (The Ukrainian Scientific Medical Youth Journal, 2025)
Payr’s disease is a rare congenital isolated splanchnoptosis, the diagnostic search of which is a challenge for the doctor. Differential diagnosis of this nosology with other diseases of the gastrointestinal tract is important, because the successful determination of treatment tactics depends on it. The described clinical case demonstrates the relevance of congenital diseases of the gastrointestinal tract, which can lead to abdominal pain syndrome.